Effect of preformed foot orthoses in reducing pain in children with juvenile idiopathic arthritis: a multicentre randomized clinical trial. (14th October 2021) - Fellas, Antoni; Singh-Grewal, Davinder; Chaitow, Jeffrey; Santos, Derek; Clapham, Matthew; Coda, Andrea
Abstract: Objectives: The aim of this study is to investigate the effect of customized preformed foot orthoses on pain, quality of life, swollen and tender lower joints and foot and ankle disability in children with JIA. Methods: Parallel group design. Children diagnosed with JIA were recruited from the three children's hospitals in New South Wales, Australia. Participants were randomly assigned to a control group receiving a standard flat innersole (sham) with no corrective modifications. The trial group were prescribed a preformed device that was customized based on biomechanical assessments. Pain was the primary outcome and was followed up to 12 months post intervention. Secondary outcomes include quality of life, foot and ankle disability and swollen and tender joints. A linear mixed model was used to assess the impact of the intervention at each time point. Results: Sixty-six participants were recruited. Child-reported pain was reduced statistically and clinically significant at 4 weeks and 3 months post intervention in favour of the trial group. Statistical significance was not reached at 6 and 12-month follow-ups. Quality of life and foot and ankle disability were not statistically significant at any follow-up; however, tender midfoot and ankle joints were significantly reduced 6 months post intervention. Conclusion: Results of this clinical trial indicate customized preformed foot orthoses can be effective in reducing pain and tender joints in children with JIA exhibiting foot and ankle symptoms. Long-term efficacy of foot orthoses remains unclear. Overall, the trial intervention was safe, inexpensive and well tolerated by paediatric patients. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR): 12616001082493.